2020
DOI: 10.1136/jim-2020-001354
|View full text |Cite
|
Sign up to set email alerts
|

Mir-30B-5P Inhibits Proliferation and Promotes Apoptosis of Medulloblastoma Cells via Targeting Myb Proto-Oncogene like 2 (Mybl2)

Abstract: Medulloblastoma (MB) is the most common malignant brain tumors among children. MiR-30b-5p is a potential tumor suppressor in a variety of human cancers. However, its expression and function in MB remain poorly understood. This study aimed to investigate the expression, role and regulatory mechanism of miR-30b-5p in MB. The expression of miR-30b-5p in MB tissues and cell lines was detected by real-time PCR. The effects of miR-30b-5p on cell proliferation and apoptosis were monitored by CCK-8 (Cell Counting Kit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Overexpression of MYBL2 correlates with poor prognosis in numerous cancers [ 43 ], including breast cancer [ 44 , 45 , 46 ]. Recent studies have shown that MYBL2 was negatively regulated by mir-30b-5p in medulloblastoma [ 47 ]. NAV1 was reported to be significantly hypomethylated in ER+/PR+ breast cancers [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of MYBL2 correlates with poor prognosis in numerous cancers [ 43 ], including breast cancer [ 44 , 45 , 46 ]. Recent studies have shown that MYBL2 was negatively regulated by mir-30b-5p in medulloblastoma [ 47 ]. NAV1 was reported to be significantly hypomethylated in ER+/PR+ breast cancers [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…MiR-30b-5p exhibited both tumor suppressor and tumor promotion functions in various tumors. A grow body of research reported that miR-30b-5p suppressed malignant behaviors of esophageal squamous cell carcinoma, malignant glioma, liver cancer, renal cell carcinoma [35][36][37][38][39] . However, Wu et al 40 found that miR-30b-5p promoted the proliferation, migration and invasion of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, by a series of bioinformatics analyses and experiments, we identified that miR-30b was the downstream target of MRPL23-AS1. miR-30b belongs to miR-30 family, is a well-studied tumor suppressor in various human cancer types, including colorectal cancer [ 18 ], gastric cancer [ 19 ], medulloblastoma [ 20 ], hepatocellular carcinoma [ 21 ], esophageal squamous cell carcinoma [ 22 ] and OS [ 23 ]. Here, we also detected the level of miR-30b in OS tissues and normal tissues, found that it was dramatically decreased in OS tissues, and this phenomenon was also observed in OS cell lines.…”
Section: Discussionmentioning
confidence: 99%